2017
DOI: 10.1021/acs.iecr.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Surface Tension Model for Prediction of Interfacial Speciation of CO2-Loaded Aqueous Solutions of Monoethanolamine

Abstract: A thermodynamic platform in combination with experimental surface tension data is used to predict the surface phase speciation of CO2-loaded aqueous solutions of 30 wt % (%) monoethanolamine (MEA) at 20, 40, and 60 °C from their corresponding bulk phase speciation. The osmotic coefficient dependency of the surface tension of an electrolyte solution has been employed to estimate the surface tension. In order to calculate the osmotic coefficients, the Pitzer equation for the excess Gibbs energy was applied. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…An increase in carbon loading which increases the μ and σ values of the solution was observed (Han et al 2012;Amundsen et al 2009;Weiland et al 1998;Zhang et al 2015) and is shown in (Idris et al 2017). The formation of carbamate, carbonate and bicarbonate after the absorption process results in increased surface tension (Matin et al 2017). In general, low viscosity and low surface tension favour the CO 2 absorption kinetics.…”
Section: Effect Of Carbon Loading On Dynamic Viscosity and Surface Tensionmentioning
confidence: 88%
“…An increase in carbon loading which increases the μ and σ values of the solution was observed (Han et al 2012;Amundsen et al 2009;Weiland et al 1998;Zhang et al 2015) and is shown in (Idris et al 2017). The formation of carbamate, carbonate and bicarbonate after the absorption process results in increased surface tension (Matin et al 2017). In general, low viscosity and low surface tension favour the CO 2 absorption kinetics.…”
Section: Effect Of Carbon Loading On Dynamic Viscosity and Surface Tensionmentioning
confidence: 88%
“…Owing to the extensive use of fossil fuel in modern industries, a quantity of carbon dioxide (CO 2 ) is discharged to the atmosphere, resulting in many environmental issues, such as the abominable greenhouse effect. At the moment, one of the most economical and effective techniques for postcombustion CO 2 capture is the amine-based solution absorption method. Aqueous monoethanolamine (MEA) (5 M, 30 wt %) solution has been considered as the benchmark for this method. However, the amine solvent absorption method requires a large amount of heat duties for CO 2 desorption, which contributes to more than 50% of the operation costs in a CO 2 capture unit. The heat duty associated with the rich amine solvent regeneration remains the most critical challenge for the large-scale implementation of this method for CO 2 capture. Despite considerable efforts to decrease energy consumption of regeneration, including modifying process configurations and using new amine formulation, advanced technology of overcoming this obstacle is still strong demanded. …”
Section: Introductionmentioning
confidence: 99%
“…Stability requirements during the dispersion processing and the printing process depend on the physical properties, such as the viscosity, and its deposition quality depends on controlling the fluid dynamics of the deposited fluids and the underlying mechanisms 2 , 3 . Moreover, the wettability is a relevant physical property for processes where droplet impingement, thin film flows, microfluidics, surface speciation and heat transfer are implied 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%